Genotype by sex interaction at different phases during Nile tilapia culture period - Yoshida, Grazyella Massako [UNESP]; Oliveira, Carlos Antonio Lopes De; Kunita, Natalã Miwa; Rizzato, Gabriel Soriani; Alexandre, Luiz; Ribeiro, Ricardo Pereira (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
Co(variance) components and genetic parameters were estimated for performance and morphometric traits in male and female Nile tilapia at different growth periods to verify the need for separate selection programs for the two genders. Data set contained information on 1,720 animals, collected in cage system. Two-trait analyses using Bayesian methodology were conducted and the records of males and females were considered distinct traits. Rates of additive genetic variance, phenotypic and heritability were higher for females in estimates for morphometric traits and higher for males in performance traits. Whereas common hatchery environment showed higher relative importance for males, the nursery caused greater variations in females. The reduction of the genetic correlation rates caused by growth increased the difference between genders and indicated the treatment of males and females as a distinct feature selection.

Estimação de componente de co(variância) e parâmetros genéticos foram obtidos para as caracterÃsticas de desempenho e morfométricas de machos e fêmeas de tilápias do Nilo em diferentes perÃodos de cultivo, a fim de verificar a necessidade de programas de seleção distinto para os sexos. O conjunto de dados continha informações de 1.720 animais, coletadas em quatro biometrias e sistema de tanques rede. Realizaram-se análises bicarácter, utilizando a metodologia bayesiana e consideraram-se os registros de machos e fêmeas como caracterÃsticas distintas. Os valores de variância genética aditiva, fenotÃpicas e herdabilidade foram maiores para as fêmeas nas estimavas para as caracterÃsticas morfométricas e maiores para os machos nas caracterÃsticas de desempenho. Nos machos, o ambiente comum de larvicultura apresentou maior importância relativa. No entanto, nas fêmeas, o ambiente que causou maior variação foi o de alevinagem. As reduções dos valores de correlação genética com o avanço do perÃodo de cultivo acentuaram as diferenças entre os sexos e indicaram a necessidade de tratar machos e fêmeas como caracterÃsticas de seleções distintos.
Interação genótipo e sexo em diferentes fases do perÃodo de cultivo de tilápias do Nilo
Keywords: Oreochromis niloticus; sexual dimorphism; Bayesian inference; Oreochromis niloticus; dimorfismo sexual; inferência bayesiana